Does intervention engagement mediate physical activity change in a web-based computer-tailored physical activity intervention?—Secondary outcomes from a randomised controlled trial - Vandelanotte, Corneel; Short, Camille E.; Plotnikoff, Ronald C.; Schoeppe, Stephanie; Alley, Stephanie J.; To, Quyen; Rebar, Amanda L.; Duncan, Mitch J. (Frontiers in Digital Health, 2024)
The relationship between intervention engagement and behaviour change may vary depending on the specific engagement metric being examined. To counter this composite engagement measures may provide a deeper understanding of the relationship between engagement and behaviour change, though few studies have applied such multidimensional engagement metrics. The aim of this secondary analysis of RCT data was to examine how a composite engagement score mediates the effect of a web-based computer-tailored physical activity intervention. Methods: 501 inactive Australian adults were randomised to a no-treatment control or intervention group. Intervention participants received 8 sessions of web-based personalised physical activity advice over a 12-week intervention period and the ability to complete action plans. Change in physical activity was assessed using Actigraph accelerometers at baseline, 3-months and 9-months. Engagement with the intervention (i.e., a composite score including frequency, intensity, duration and type) was continuously assessed during the intervention period using website tracking software and database metrics. Generalised structural equation models were used to examine how a composite engagement score mediated intervention effects at 3 months and 9 months. Results: At 3 months, mediation analysis revealed that the intervention group had significantly higher engagement scores than the control group (a-path exp(b)=6.462, 95%CI=5.121-7.804, p<0.001). Further, increased engagement with the intervention platform was associated with an increased time spent in moderate-to-vigorous physical activity (ab-coefficient exp(b)=1.008, 95%CI=1.004-1.014, P<0.001); however, the magnitude of this effect was small. There were no significant mediation effects at the 9-month time point. Discussion: The findings suggest that a composite intervention engagement score has a small positive influence on physical activity changes and that other factors (e.g., behaviour change techniques) are likely to be more important drivers of behaviour change. Deleted: study Moved down [1]: For the intensity component, the 289 calculation integrates activity session (1 to 8) and action 290 plan (1 to 6) completion status into the score of the291week these were meant to be completed, so by design 292 the weekly intensity score will increase on weeks when 293 these tasks were scheduled (see Table 1). ¶